Effects of SiON/III-nitride interface properties on device performances of GaN-based power field-effect transistors. (22nd October 2020) - Sun, Zhonghao; Huang, Huolin; Wang, Ronghua; Liu, Yanhong; Sun, Nan; Li, Feiyu; Tao, Pengcheng; Ren, Yongshuo; Song, Shukuan; Wang, Hongzhou; Li, Shaoquan; Cheng, Wanxi; et al.
Abstract: In this work, we performed an investigation on the electrical characteristics of the interfaces of SiON/AlGaN and SiON/GaN by fabricating a partially gate-recessed metal-insulator-semiconductor high electron mobility transistor (MIS-HEMT) and a fully gate-recessed metal-insulator-semiconductor field-effect transistor (MIS-FET). The fabricated MIS-HEMT exhibits a smaller static on-resistance ( R on ) of 12.7 Ω · mm, while the MIS-FET achieves the normally-off operation. As a result of over-etching in the gate trench, a higher trap state density of 2 × 10 13 cm −2 eV −1 at the SiON/GaN interface in comparison to SiON/AlGaN interface (8 × 10 12 cm −2 eV −1 ), leading to a more obvious degradation of subthreshold swing, was extracted after performing the high temperature I DS − V GS tests. In addition, compared with the MIS-FET, the traps distributed at the SiON/AlGaN interface are found to be located at a deeper energy level, which make the device more stress sensitive and can cause a greater threshold voltage ( V th ) shift in the drain-bias stress measurement. The drain-bias stress at off-state increases the ionized trap density and makes the ionized traps unrecoverable within 1000 s in the MIS-HEMT. This work reveals the different properties of traps states at the SiON/AlGaN and SiON/GaN interfaces, and their effects on the device reliability.